E-Servqual dan Model Kano dalam Aplikasi M-Tix - Untono, Selomit Aron Gita; Sumiati, Sumiati (Ekonomis: Journal of Economics and Business, 2025)
The study aims to determine the extent of user satisfaction of the M-Tix application on Android devices. User satisfaction analysis was conducted using the E-Servqual method and the Kano Model. The data collection method was carried out by distributing questionnaires to 100 respondents who met the criteria with 21 research attributes describing the E-Servqual Dimension. The results showed that there were 3 attributes that had satisfied M-Tix Application users. 18 attributes still needed to be improved, because they had a negative E-Servqual Gap. Attributes categorized as category M were 10 attributes. Attributes with category A had 9 attributes. Meanwhile, attributes categorized O and I each had one attribute. Based on this, there were 3 attributes that needed to be maintained, 17 attributes that needed to be improved, while the remaining one attribute could be removed.